ANALISIS PERCAKAPAN PADA KOMUNIKASI HATI DALAM FILM NANTI KITA CERITA TENTANG HARI INI (NKCTHI) - Fairuz Elsa Arlene Zahidah, (2023)
This study aims to determine the description of family conflict in communication studies in the film Nanti Kita Cerita Tentang Hari (NKCTHI). how the emphasis of drama in a film by analyzing the heart communication model. The method used in this research is a method with conversation analysis, which is a method that focuses on the practice of speaking in conversations. In this method, all characters' conversations are analyzed using the modality of communication. Based on the results of the study, the conflict that occurred in Mr. Narendra's family was caused by a sense of selfishness, and there is also a lack of open communication among family members. These barriers cause unbalanced communication patterns and lead to conflict. Conflicts that occur in NKCTHL conversation scenes arise when there are differences in ego statements, namely Parent-Adult-Child Ego, Parent-Child Ego, and Adult-Child Ego. Meanwhile, conflict does not arise when there is a Staten ego equation in the conversation. The researchers suggest that conflict occurs when everyone in the conversation can be open to each other, willing to empathize and sympathize with others. Equal and open communication patterns can be done with heart communication such as empathy, care, sympathy, appreciation, and honesty so that conflict will not arise